Difficulties of Grade X students in learning Trigonometry (Siddhajyoti Interdisciplinary Journal, 2021)
Abstract This paper aims to explain the difficulties of grade X students in learning trigonometry that were explored from an empirical study in the year 2017 AD. The researcher used explanatory mixed research design where 155 students of grade X were selected randomly from the four schools of Kirtipur municipality to conduct initial survey to find low achievers and most difficult content areas of trigonometry by using achievement test. Then five low achievers and respective three mathematics teachers were selected and interviewed with the help of semi-structured interview guidelines to explore what difficulties had they experienced and encountered in learning trigonometry. The results revealed that mean achievement score of students in institutional schools was greater than that of students of community schools. However, there are some common areas of difficulties of students in both types of schools for learning trigonometry including the difficulties related to memorization of facts; comprehension of new concepts; transformation of verbal problems; derivation and proofs of trigonometric relations and unfamiliarity with the solving process of problems in application level. These difficulties are due to several reasons including abstract nature of contents, poor prerequisites among students, demonstration of teacher centered instruction, and focusing on rote memorization rather than conceptual understanding. Hence, it is recommended that both students and teachers need to focus on conceptual learning rather than rote memorization for meaningful understanding in trigonometry.